Natural Coloring Innovation: Analysis of Ecoprint Process on Leather at NURB Leather Gallery Malang - Sutrisno, Julia Dwi Ananda Putri; Sumarwahyudi (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
NURB leather gallery is located at Jl Danau Belayan V block C 4D No 1 Malang. Producing ecoprints with leather media whose results are applied in products of various designs of women's bags, wallets, and accessories. This place has never done research about it. This research will focus on: 1) to describe the process of preparing leather media for ecoprint. 2) To describe the process of ecoprinting on leather media. 3) to describe the result of ecoprint on leather media. This research uses a qualitative approach that is described descriptively. Data collection methods in this research are using interviews, participatory observation and documentation. Checking the validity of the data in this study is using the triangulation method. NURB Leather Gallery was established by Nurbeti in 2014. This gallery uses several types of leather, mainly using sheepskin as the main material because it is easy to process in making ecoprints. The leather ecoprint process in this gallery includes six steps. The prints of teak leaves, green castor, cosmos, ulung blood, AMP flowers, cosmos flowers, and red frangipani flowers are clearly visible with sharp leaf veins. Meanwhile, the lanang, vitex, jarak kepyar, red panama, and teak leaves are quite clear, while the curry leaves look faint. Overall, however, the varied combination of print treads makes ecoprinting with leather media unique.